HEALTH ASPECTS OF INDUSTRIALIZATION - A.Ghiami (Tehran University of Medical Sciences, 1973)
Any form of industrialization leads to cultural changes which may be rapid and extensive, and provoke considerable stress. Such changes are particularly extensive when developing countries are rapidly industrialized. Agricultural workers who move to industrial areas may shift from barter to a monetary economy. All of this is to them an entirely new way of living and so they try to keep contact with their place of origin. As a result their new life in the city and at home is disrupted. The traditional Social Forces and moral values which formerly exercised a stabilizing influence in the peasant culture are weakened. The result may be social disorganization which can have far reaching effects on community health and lead to behavioral disorders such as delinquency, crime, drug addictions and alcoholism and contribute to an increase in incidence of mental illness. During the period of industrialization the increase of food production may not be of the same order as the increase in production of industry. With the transfer of the population from rural areas to the industrial centers some changes of diet may occur. The health problems of the workers will often be related not only the environment. The workers might be exposed to hazardous physical, chemical and biological factors.